Challenges and opportunities for workforce skills in halal agri-food sector to meet global market demands through Halalink application - Indriani, Mutiara Rachmina; Arrahman, Naufal; Dini, Vianda Mayeri; Rahmawati, Yuli; Darmawan, Noviyan (Halal Studies and Society, 2025)
Indonesia is the largest Muslim-majority country in the world and holds significant potential in halal food farming sector. The growing global demand for halal products offers vast opportunities to expand agricultural exports and meet the needs of both domestic and international markets. However, challenges such as a lack of skilled human resources, limited awareness of halal certification processes, and technological barriers, particularly among micro, small, and medium enterprises (MSMEs), hinder the industry growth. Therefore, this study aimed to develop "Halalink," an innovative mobile application designed to address challenges by promoting halal education, collaboration, and compliance with standards. Halalink has three features including (i) Halalearns, with educational content about halal standards, (ii) Halalabs for collaboration among stakeholders, and (iii) Halalassists, which offers continuous guidance to ensure compliance with halal regulations. In conclusion, Halalink is a sustainable solution to enhance public awareness, simplify halal certification process, as well as build a competitive and ethical halal agri-food sector in Indonesia.